PROXIMAL MYOTONIC DYSTROPHY MIMICKING PROGRESSIVE MUSCLE WASTING. Issue 12 (15th November 2016) - Hosseini, Akram A.; Chaal, Sangeeta; Mann, Carl
Abstract : Introduction: Progressive myotonic dystrophy is a distinct entity from proximal myotonic myopathy, and can present with unusually prominent muscle atrophy, proximal weakness and absence of clinical myotonia. Progressive muscle wasting should to be differentiated from motor neuron disease (MND) along with other causes. Case Presentation: A 56-year old man presented to the spinal team with weakness in his legs, difficulties in walking uphill and a lower backache. Spinal MRI was unremarkable, however, nerve conduction studies reported a diffuse active denervation suggesting MND. He was then referred to the neurology team. Re-examination by a Neurologist found proximal muscle wasting, but unable to observer any fasciculations, tongue atrophy, upper motor neuron signs or clinical myotonia. Doubting a diagnosis of MND, electrophysilogical studies were repeated which showed diffuse spontaneous activity and myotonic discharges. Genetic testing confirmed an expansion in the DMPK gene with an unstable range of 96 repeats and a final diagnosis of myotonic dystrophy type 1 was made. The patient later obtained new information and reported a family history of myotonic dystrophy in his paternal cousins. Conclusion: Considering the extreme clinical heterogeneity of the myotonic dystrophies, a careful clinical examination and EMG studies should be performed in patients with unusually progressive muscle atrophy and weakness.